Metode K.Means Clustering dalam Persebaran Covid 19 di Sumatra Barat - meri, rozi (STKIP PGRI Sumatera Barat, 2021)
Corona virus is a positive single strain RNA virus that infects the respiratory tract. Diagnosis starts from general symptoms in the form of fever, cough and difficulty breathing. One of the causes of the very high spread of the corona virus is due to physical contact with positive COVID patients. There are many impacts of the increasing corona virus in various countries, one of which is Indonesia. The high rapid spread of the corona virus has reached regional areas including the province of West Sumatra, therefore it is very necessary during this pandemic to keep your distance and stay away from crowds and comply with health protocols and stay away from areas that have a high spread of the corona virus. grouping or clusters of the spread of the corona virus in the West Sumatra region using the k-means clustering data mining method. The study was conducted using the variables confirmed, died, recovered and the number of positive . based on data that has been processed and produces information that can be expected to help the government to take decisions or actions to reduce the spread of the Corona virus in the West Sumatra region.